Analysis Implementation of Hospital Management Information System (SIMRS) at Place of Inpatient Registration (TPPRI) Using The PIECES Method at The Ajibarang Government Hospital - Afgani, Abu Sofyan Al; Indira, Zahrasita Nur; Nadi, Danu Tirta; Marini, Budiana (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2024)
Hospital Management Information System (SIMRS) is an information communication technology system that processes and integrates the entire process flow of hospital services in the form of a network of coordination, reporting and administrative procedures to obtain information precisely and accurately, and is part of the Health Information System. The implementation of SIMRS at the Ajibarang Regional General Hospital (RSUD) has been carried out since 2014 in almost all units, one of which is the Inpatient Registration Place (TPPRI). This study aims to improve the shortcomings of the system that has been made at SIMRS RSUD Ajibarang. The method used in this study is qualitative. The data collection method used in this study was using in-depth interviews. The data analysis method uses Performance, Information, Economy, Control, Efficiency, and Service (PIECES) which aims to obtain information related to the implementation of SIMRS at the Ajibarang Regional General Hospital. Based on the results of the SIMRS analysis in the TPPRI section, there are still obstacles in its implementation, both in terms of Performance, Information, Economy, Control, Efficiency, and Service. The results showed that there are still several problems, namely the presence of menus that are not functioning optimally, different TPPRI and TPPRJ SIMRS, inaccurate data, Human error, server down, and no warning if an error occurs. SIMRS has been running according to user needs, but cannot be separated from various problems, so it is necessary to improve and develop SIMRS through researcher recommendations so that SIMRS can maintain and improve the quality of service to patients. Based on the description of the problem, as there is no warning if an error occurs, the user will easily continue to input data on SIMRS so that errors are not detected that result in losses for hospitals and produce inaccurate data.